Effect of job satisfaction on employee productivity in selected manufacturing companies in Oyo State, Nigeria - Philip Adekanmbi, Foluso; I Ukpere, Wilfred; O Adegoke, Steve (International Journal of Psychosocial Rehabilitation, 2024)
Research purpose: The reason for this paper is to investigate the effect of job satisfaction on employee productivity in selected manufacturing companies in Oyo State, Nigeria. Research approach/design and method: The present paper adopted a quantitative research approach as well as a survey research design. Main findings: The empirical outcomes of the current paper showed that the stages of job satisfaction (high and low) strongly predict employee productivity in the manufacturing industry in Oyo State, Nigeria. Also, the current investigation showed that work experience has a significant influence on employee productivity in the manufacturing industry in Oyo State. Furthermore, the study revealed that there is a significant gender influence on employee productivity in the manufacturing industry in Oyo State, Nigeria. Practical implications: The outcomes of the present investigation have major inferences for positive employee behaviour management, employee productivity, and economic growth within the Nigerian manufacturing industry. Originality/Value: This investigation is distinctive, as it significantly contributes to the entity of knowledge regarding appropriate management strategies to achieve a significantly high level of job satisfaction and employee productivity, not merely in the world of production work but specifically in Oyo State, Nigeria. Hence, the study highlighted the aiding potentials of job satisfaction, age, work experience, level of education, and gender when increasing employee productivity.